Transformasi Pendidikan Kewarganegaraan di Hong Kong: Dari Studi Liberal ke Kewarganegaraan dan Pembangunan Sosial - Syams, Muhammad Syamsuddin (Yayasan Penelitian Dan Pengabdian Masyarakat Sisi Indonesia, 2025)
ABSTRACT This study examines the transformation of Hong Kong’s citizenship curriculum from Liberal Studies to Citizenship and Social Development (CSD) as a case of deliberate educational repoliticization. Using a qualitative literature-based approach that analyzes curriculum documents and scholarly sources, the research identifies how CSD replaces critical, inquiry-based learning with state-directed instruction emphasizing national loyalty and a simplified national narrative. Unlike previous studies that primarily describe policy shifts, this research contributes a theoretical perspective by framing curriculum change as an ideological state apparatus that narrows reflective and participatory spaces in semi-authoritarian contexts. The findings reveal that, despite these constraints, students still exercise symbolic agency subtle forms of resistance or reinterpretation of official narratives within the classroom. This highlights the dual nature of civic education as both a tool of state control and a site of contested meaning. The study recommends safeguarding academic freedom, integrating critical thinking and dialogue into the curriculum, and empowering teachers with greater pedagogical autonomy to ensure that civic education nurtures informed, critically engaged citizens.